Criticism of Feminist Ideology in Surah An-Nisa Verse 34 - Muhammad Kamaluddin; Mohammad Adibul Umam; Husnul Fikri; Saidul Hafizi (Penerbit Hellow Pustaka, 2025)
This research examines the critique of feminist ideology in QS. An-Nisa verse 34. In that verse, a man (husband) is responsible for a woman. (istri). Historically, this decree has been interpreted since the revelation of the verse until now. By using the library research method and through a descriptive analysis approach, this study delves deeper into the critique of feminist ideology present in that verse. The analysis results show that women and men have complementary roles in the household, so whoever the leader of the household is, as long as they possess the ability to be responsible for their family, whether the wife or husband, they can become the leader as long as they uphold the principles of sakinah, mawaddah, and rahmah to maintain harmony in the family.